Chứng minh: a. x ² + x + 1 > 0 b. (x – 3)(x – 5) + 2 > 0 c. x ² + y ² + 2xy + 4 > 0 d. 4x – 10 – x ² < 0 e. -x ² + 4x – 5 < 0 f. x ² + 2x + y ² + 1 ≥

Chứng minh:
a. x ² + x + 1 > 0
b. (x – 3)(x – 5) + 2 > 0
c. x ² + y ² + 2xy + 4 > 0
d. 4x – 10 – x ² < 0
e. -x ² + 4x – 5 < 0
f. x ² + 2x + y ² + 1 ≥ 0
g. 4( x – 2 )( x – 1 )( x + 4 )( x + 8 ) +25x ² ≥ 0
giúp vwois ạ plsssss

0 thoughts on “Chứng minh: a. x ² + x + 1 > 0 b. (x – 3)(x – 5) + 2 > 0 c. x ² + y ² + 2xy + 4 > 0 d. 4x – 10 – x ² < 0 e. -x ² + 4x – 5 < 0 f. x ² + 2x + y ² + 1 ≥”

  1. Giải thích các bước giải:

    $\begin{array}{l}
    a){x^2} + x + 1 = {\left( {x + \frac{1}{2}} \right)^2} + \frac{3}{4} > 0,\forall x\\
    b)\left( {x – 3} \right)\left( {x – 5} \right) + 2 = {x^2} – 8x + 17 = {\left( {x – 4} \right)^2} + 1 > 0,\forall x\\
    c){x^2} + {y^2} + 2xy + 4 = {\left( {x + y} \right)^2} + 4 > 0,\forall x,y\\
    d)4x – 10 – {x^2} =  – \left( {{x^2} – 4x + 10} \right) =  – {\left( {x – 2} \right)^2} – 6 < 0,\forall x\\
    e) – {x^2} + 4x – 5 =  – \left( {{x^2} – 4x + 5} \right) =  – {\left( {x – 2} \right)^2} – 1 < 0,\forall x\\
    f){x^2} + 2x + {y^2} + 1 = {\left( {x + 1} \right)^2} + {y^2} \ge 0,\forall x,y\\
    g)4\left( {x – 2} \right)\left( {x – 1} \right)\left( {x + 4} \right)\left( {x + 8} \right) + 25{x^2}
    \end{array}$

    Bạn xem lại đề câu g 

    Reply

Leave a Comment